Relation of plasma matrix metalloproteinase-8 levels late after myocardial infarction with left ventricular volumes and ejection fractio - Ayhan Erkol; Selçuk Pala; Vecih Oduncu; Alev Kılıcgedik; Filiz Kızılırmak; Can Yücel Karabay; Ahmet Güler; Cevat Kırma (KARE Publishing, 2013)
Objectives: Enhanced matrix metalloproteinase-8 (MMP-8) activity in the early post-myocardial infarction (MI) period has been related to early remodeling. However, it has been demonstrated that plasma MMP-8 level has a biphasic profile, and the relation between the late plasma levels and remodeling is unclear. We evaluated the plasma MMP-8 levels and its correlates 20+-3 months after acute MI. Study design: 58 post-MI patients and 26 control subjects underwent quantitative single-photon emission computed tomography (SPECT) and echocardiography. The plasma MMP-8 levels were measured and its correlates were investigated. Results: The MMP-8 levels were significantly higher in post- MI patients [median 3.88 ng/ml, interquartile range (1.88- 6.43) vs. 0.67 ng/ml (0.34-2.47); p<0.001]. Plasma MMP-8 levels were significantly correlated with left ventricular ejection fraction (LVEF) (ρ=0.34, p=0.009), end diastolic volume index (EDVi) (ρ=-0.39, p=0.002) and end systolic volume index (ESVi) (ρ=-0.40, p=0.002). Conclusion: Plasma MMP-8 levels were found to still be high in post-MI patients 20+-3 months after the index event. The levels were significantly correlated with left ventricular volume indices and LVEF. We speculate that, in contrast to the relation between the higher early MMP-8 activity and the extent of cardiac remodeling, higher late levels may be associated with relative preservation of left ventricular systolic function.